Microseismic positioning of an isolated working face under complex geological conditions and its engineering application - Long, Zhao (Frontiers in Earth Science, 2023)
In view of the inability to accurately locate vibrations in isolated workings under complex geological conditions, an adaptive rotational categorization method, a downhill comparison method based on time-frequency analysis (TFA-DC method), a variable-step acceleration search method, and a dual-phase seismic source location method(TD-DL method) are proposed. A set of integrated software with features of "visualization", "interactive" and "one-click" was developed for microseismic data processing. Results show that the recognition accuracy of the adaptive rotational categorization method is improved by 4.8% under the engineering example of the isolated working face of Tashan mine, and the TFA-DC method compares with the improved STA/LTA method. The former can pick up both the P-wave precise arrival time and the S-wave peak arrival time while the latter can only pick up the P-wave precise arrival time, and the arrival-time-picking-failure ratio for the is 0 while for the latter it is 15.63%. The standard deviations of the objective function value, the localization error, and the wave-velocity error of the step acceleration search method are all 0. The mean localization error of the TD-DL method is 9.5% and 14.5% of the P-wave and the S-wave single-phase localization, respectively. The TD-DL method improved the ability to combine the known information such as the geophone coordinates and dual-phase arrival times, so that the localization results tend to be on the side of two single-phase the localization results with smaller errors than those of the real source. This, to some extent, counteracts the localization errors obtained from the P-wave and the S-wave single-phase calculations, thus achieving the effect of improving the accuracy of source inversion positioning.